ANALYSIS OF STUDENTS UNDERSTANDING OF GEOMETRY CONCEPTS THROUGH LEARNING BY GIVING SCAFFOLDING - Cindy Fildza Lubis; Muhammad Amin Fauzi (Berajah Journal, 2022)
This study aims to determine: (1) the effect of learning by giving scaffolding on students' understanding of geometric concepts, (2) the improvement of students' understanding of geometry concepts taught through learning by giving scaffolding, (3) the advantages of learning by giving scaffolding, and (4) the disadvantages of learning by giving scaffolding. This type of research includes descriptive qualitative research using library research methods. The data in this study were obtained from a collection of literature such as theses and journals that are relevant to the topic of discussion, namely understanding students' geometric concepts through learning by providing scaffolding. The results show that, 1) Learning by giving scaffolding has a great effect on students' understanding of geometric concepts based on the overall effect size calculation which produces an average effect size of 0.994 where this number is included in the high category. 2) There is an increase in the students' understanding of geometric concepts that are taught through learning by giving scaffolding. This can be seen from the achievement of indicators in the experimental class in the literature which is generally better than the control class. 3) Based on the analysis, it was found that the advantages of learning by providing scaffolding are (a) Can encourage students to find the concepts independently, (b) A great motivational tool to increase students' confidence in learning geometry concepts, (c) Make students more engaged in the learning process, (d) Make students more creative to reason, (e) Potential to optimize a quality learning environment. 4) The weakness of learning by providing scaffolding is that students need to adapt to the types of scaffolding used, especially technology-based and if the teacher does not understand the scaffolding, students will experience difficulties and scaffolding also takes a relatively long time.